Enquêteur ou espion ? Une organisation de recherche aux prises avec la défiance (le Mass Observation, 1939-1945) - Ariane Mak (Tracés, 2016)
This article shows how social research investigators from Mass Observation experienced first-hand the acute suspicion that swept Britain during the Second World War. These were times when governmental propaganda insisted that “careless talk costs lives”, when the general public was acutely spy-wary, when the fear of Fifth columnists was widespread. In this context, the mere sight of a stranger asking questions of people in the streets, while scribbling in a notebook, was cause for suspicion. This article analyzes several accounts of investigators being mistaken for spies, and the inquiries undertaken by the police and citizens alike. Little scholarly attention has been paid to Mass Observation’s fieldwork difficulties during wartime and to the new methods the organization devised to avoid popular suspicion. By studying the grounded mechanisms of misinterpretation through a pragmatist approach we also hope to contribute to a historical anthropology of suspicion.